Air-stable MXene/GaAs heterojunction solar cells with a high initial efficiency of 9.69%. Issue 29 (19th July 2021) - Zhang, Zhijie; Lin, Jing; Sun, Peiye; Zeng, Qinghao; Deng, Xi; Mo, Youtian; Chen, Jiaying; Zheng, Yulin; Wang, Wenliang; Li, Guoqiang
Abstract : A novel MXene/GaAs heterojunction solar cell with a stabilized PCE of ∼12.5% has been achieved via a facile one-step method of drop-casting for the first time. Abstract : Two-dimensional (2D) material-based heterojunction solar cells have attracted significant interest due to their potential in low-cost photovoltaic applications. Herein, a novel MXene/GaAs heterojunction solar cell with high efficiency and excellent stability has been achieved via a facile one-step method of drop casting for the first time. The high work function of the transparent MXene and the enhanced interfacial interaction between the MXene and GaAs contribute to the formation of a high-quality Schottky diode, resulting in a high initial power conversion efficiency (PCE) of 9.69%, surpassing those of other reported 2D material/semiconductor heterojunction solar cells. Moreover, after the deposition of a ZnS/MgF2 composite coating, the as-prepared MXene/GaAs heterojunction solar cell exhibits an average PCE of 12.5% with stability over 30 days in air. This work is of great importance for obtaining high-efficiency and air-stable solar cells for light-harvesting for sustainable development.